The combined effects of elevated pCO2 and food availability on Tigriopus japonicus Mori larval development, reproduction, and superoxide dismutase activity. (January 2018) - Li, Fei; Shi, Jiahui; Cheung, S.G.; Shin, P.K.S.; Liu, Xiaoshou; Sun, Yan; Mu, Fanghong
Abstract: Previous studies have shown that ocean acidification has little effect on adult Tigriopus japonicus copepods, and mainly impairs the early development and reproduction of females. This study investigated the possible interactive effect between CO2 -induced seawater acidification and food availability on larval development and reproductive output in T. japonicus . Copepods were exposed to either pH 8.1 or pH 7.3 under different food concentrations (0.5 × 10 4 –80.0 × 10 4  cells/mL). Both the development of nauplii and copepodites was delayed at pH 7.3 with a greater effect at lower food concentrations. The reproductive output followed a bell-shaped curve with the highest reproductive output at food concentrations between 30 × 10 4 and 40 × 10 4  cells/mL. As an indicator of oxidative stress, the activity of superoxide dismutase increased at lower pH, with a greater increase at lower food concentrations. Therefore, the effect of elevated p CO2 on T. japonicus was food dependent. Highlights: Both food scarcity and elevated p CO2 prolonged the larvae development of T. japonicus . Reproductive output decreased under lower pH The effect of food followed a bell-shape curve with a lower reproductive output at food concentrations Higher SOD activity in individuals exposed to seawater acidification under low food concentrations. Increased food availability might prepare copepods to cope with oxidative stress caused by the lowering of pH.